2020
DOI: 10.5114/ada.2020.98285
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3, p53 and Bcl-2 expression in basal cell carcinoma of the eyelid

Abstract: Introduction: Eyelid tumours mostly originated from skin and its appendeges. External carcinogens like UV radiation causes cell damages in the eyelid skin and contributes to carcinogenesis. Apoptosis is a very important mechanism to prevent these damage and probable neoplatic change. Aim: To compare caspase-3, p53 and Bcl-2 levels between patients with basal cell carcinoma (BCC) of the eyelid and healthy individuals. Material and methods: Pathology archives from October 2012 to April 2015 were scanned for BCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Several stimuli, including hormones, cytokines, growth factors, and immunological responses, can influence the apoptosis process. The presence of cells expressing active caspase 3 is regarded as a marker of apoptotic activation [53,54]. Furthermore, it has been demonstrated that the p53 proteins play a critical regulatory role in apoptosis [40,53].…”
Section: Discussionmentioning
confidence: 99%
“…Several stimuli, including hormones, cytokines, growth factors, and immunological responses, can influence the apoptosis process. The presence of cells expressing active caspase 3 is regarded as a marker of apoptotic activation [53,54]. Furthermore, it has been demonstrated that the p53 proteins play a critical regulatory role in apoptosis [40,53].…”
Section: Discussionmentioning
confidence: 99%
“…The tissue sections taken to poly-L-lysine coated slides were stained in CD117/c-kit (Biocare Medical PME296AA) 1:50, MMP2 (GeneTex GTX14577) 1:200, caspase-3 (GeneTex GTX73090) 1:1000 antibody dilutions by immunohistochemistry (IHC) method after deparafinization according to the reference (Koyun et al, 2020).…”
Section: Methodsmentioning
confidence: 99%